Optimization of anticoagulant therapy in patients undergoing mechanical heart valve replacement - S. A. Tkachenko; D. A. Astapov; A. V. Bogachev-Prokofiev; A. S. Zalesov; A. N. Pivkin; A. G. Makaev; Kh. A. Agaeva; R. M. Sharifulin (Фундаментальная и клиническая медицина, 2023)
Acquired heart defects have a high prevalence among patients of different age groups and represent a significant social problem. To date, surgery remains the only effective option to treat acquired heart disease, and replacement of the dysfunctional heart valves frequently relies on mechanical prosthetic heart valves which implantation requires lifelong anticoagulant therapy with vitamin K antagonists and constant monitoring of international normalised ratio. However, the optimal target range for international normalised ratio values remains poorly defined. Optimisation of the approaches to anticoagulant therapy for this category of patients is becoming increasingly important. This paper highlights the main problems and possible solutions for patients who have undergone implantation of mechanical heart valves and need constant intake of vitamin K antagonists.